Development of Middle East Respiratory Syndrome Coronavirus vaccines – advances and challenges. Issue 2 (1st February 2018) - Cho, Heeyoun; Excler, Jean-Louis; Kim, Jerome H.; Yoon, In-Kyu
ABSTRACT: Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is an emerging pathogen with the potential to pose a threat to global public health. Sporadic cases and outbreaks continue to be reported in the Middle East, and case fatality rates remain high at approximately 36% globally. No specific preventive or therapeutic countermeasures currently exist. A safe and effective vaccine could play an important role in protecting against the threat from MERS-CoV. This review discusses human vaccine candidates currently under development, and explores viral characteristics, molecular epidemiology and immunology relevant to MERS-CoV vaccine development. At present, a DNA vaccine candidate has begun a human clinical trial, while two vector-based candidates will very soon begin human trials. Protein-based vaccines are still at pre-clinical stage. Challenges to successful development include incomplete understanding of viral transmission, pathogenesis and immune response (in particular at the mucosal level), no optimal animal challenge models, lack of standardized immunological assays, and insufficient sustainable funding.